2020
DOI: 10.1101/2020.07.24.219923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The YtrBCDEF ABC transporter is involved in the control of social activities inBacillus subtilis

Abstract: Bacillus subtilis develops genetic competence for the uptake of foreign DNA when cells enter the stationary phase and a high cell density is reached. These signals are integrated by the competence transcription factor ComK which is subject to transcriptional, post-transcriptional and post-translational regulation. Many proteins are involved in the development of competence, both to control ComK activity and to mediate DNA uptake. However, the precise function they play in competence development is often unknow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Recent studies suggest that ABC transporters can also have a direct or indirect effect on PG biosynthesis and remodeling. For instance, it has been shown that the overexpression of the YtrBCDEF ABC transporter of B. subtilis leads to the production of a thicker PG layer [ 65 ]. The transporter YtrBCDEF is encoded in the ytrGABCDEF operon and the GntR family repressor YtrA controls its expression [ 66 , 67 ].…”
Section: Abc Transporters Affecting Cell Wall Biosynthesis and Remmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest that ABC transporters can also have a direct or indirect effect on PG biosynthesis and remodeling. For instance, it has been shown that the overexpression of the YtrBCDEF ABC transporter of B. subtilis leads to the production of a thicker PG layer [ 65 ]. The transporter YtrBCDEF is encoded in the ytrGABCDEF operon and the GntR family repressor YtrA controls its expression [ 66 , 67 ].…”
Section: Abc Transporters Affecting Cell Wall Biosynthesis and Remmentioning
confidence: 99%
“…Interestingly, the expression of the ytrGABCDEF operon was not induced in presence of acetoin [ 66 ], suggesting that the YtrBCDEF transporter might only have an indirect effect on acetoin utilization. The absence of the transcriptional regulator YtrA further led to a complete loss of genetic competence [ 65 , 78 ]. The loss of competence of the ytrA mutant could potentially be explained by an inability of the DNA to reach the competence pilus ComG due to the thicker PG layer produced by this strain [ 65 ]; however, further experiments are required to investigate this.…”
Section: Abc Transporters Affecting Cell Wall Biosynthesis and Remmentioning
confidence: 99%
See 1 more Smart Citation